Korelasi antara Pemahaman Nilai-Nilai Islami dengan Kesadaran Berbusana Muslimah Peserta Didik di SMPN 2 Bukittinggi - Laila Azmi; Iswantir Iswantir (Lembaga Yasin AlSys, 2026)
Although studies on the education of Islamic values have been widely conducted, research that specifically discusses the relationship between understanding Islamic values and awareness of Muslimah dress among junior high school students remains relatively limited. This study aims to analyze the relationship between understanding Islamic values and awareness of Muslimah dress among eighth-grade students at SMP Negeri 2 Bukittinggi. This study employed a quantitative approach with a correlational design. The research subjects consisted of 145 eighth-grade Muslimah students selected using the total sampling technique. Data were collected through a questionnaire that had been tested for validity and reliability, which included 24 statement items for the variable of understanding Islamic values and 33 statement items for the variable of awareness of Muslimah dress. The data were analyzed using Pearson Product Moment correlation with the assistance of SPSS version 20. The results showed a positive and significant relationship between understanding Islamic values and awareness of Muslimah dress, with a correlation coefficient of r = 0.623 at a significance level of 0.05. The coefficient of determination showed that understanding Islamic values contributed 38.9% to awareness of Muslimah dress, while the remainder was influenced by other factors outside this study. These findings emphasize that understanding Islamic values has an important role in shaping students’ awareness of Muslimah dress. The implications of this study indicate the importance of strengthening the teaching of Islamic values in schools to shape religious character, while also enriching the study of Islamic Religious Education regarding the relationship between the cognitive aspect of religiosity and students’ religious behavior.